Assessment of safety of additional transplantation of autologous bone marrow mononuclear cells in the combined treatment of coronary heart disease. Results from a randomized, blind, placebo-controlled trial (TAMIS) - V. V. Komok; N. S. Bunenkov; S. A. Beliy; V. M. Pizin; V. M. Kondratev; А. V. Dulaev; V. I. Lukashenko; A. E. Kobak; T. S. Maksimova; I. P. Sergienko; E. V. Parusova; L. A. Smirnova; et al. (Вестник трансплантологии и искусственных органов, 2019)
Aim: to assess the safety of transplantation of autologous bone marrow mononuclear cells when performing coronary artery bypass grafting in the combined treatment of ischemic heart disease in patients with coronary and heart failure.Materials and methods. During the period from 2013 to 2016 years 117 patients, who meet the established criteria, were included in the work. Randomization was performed in observation groups: group 0 -control group (coronary artery bypass grafting (CABG) and intramyocardial administration of a 0.9% NaCl solution), group 1 - CABG surgery and intramyocardial administration of autologous bone marrow mononuclear cells (ABMMS), group 2 - CABG surgery and intramyocardial and intragraft administration of ABMMS. Clinical, laboratory - CPK MB, myoglobin, troponin I, HCT, Hb, K +, ABC; instrumental (stress tests, echocardiography, speckle tracking, coronary angiography) data were evaluated in these groups. The analysis of the frequency of postoperative complications (hydrothorax, hydropericardium, rhythm disturbances) was performed; the length of stay in the intensive care unit, the length of stay in the hospital and other indicators. After 6 and 12 months, the overall mortality was assessed, major cardiac events - the development of acute myocardial infarction, ventricular arrhythmias, oncological alertness. Number in international register clinical trials Clinical Trial. gov Identifier: NCT02059512.Results. Statistical analysis showed no statistically significant differences in the observation groups for the compared criteria.Conclusion. Transplantation of autologous bone marrow mononuclear cells during aorto-coronary bypass surgery in the combined treatment of coronary heart disease is a safe method.